Value Chain Analysis of Ginger in Surkhet District - Acharya, Samarpan; Bhatta, Kiran Prasad; Adhikari, Anup; Chaudhary, Sunil (Journal of Agriculture and Resource Management, 2026)
Ginger is herbaceous subtropical perennial plants and is one of the important export crops. Participation of farmers in ginger value chain may bring about significant changes in their income and hence livelihoods. The study was conducted in the Bheriganga municipality of Surkhet district to assess the value chain of ginger. Household survey of 100 ginger growers was done with the semi structure questionnaire. Altogether seven traders, including four wholesalers, two retailers and one processing unit were also interviewed through the checklist. Collected data were analyzed using MS Excel. On an average the ginger cultivated area was 2.27 ropani with average cost of production and revenue to be Rs. 11,061 and Rs. 18,185 per ropani, respectively. Majority of the production cost was for seed rhizome and the BC ratio was found to be 1.6, indicating moderate returns. The average farm gate price was Rs. 35/kg whereas retail price of wholesaler and retailer was Rs. 60/kg and 90/kg, respectively (producers’ share is a meager 39%). Retailer had the highest market margin of Rs. 26.5/kg in fresh ginger chain. The price spread was Rs. 55/kg. There were also a few processing units involved in making sliced ginger which export to foreign countries (e.g. Germany). The margin of the value-added sliced ginger was found to be Rs. 226.75. At the farmer level, no value addition activities were observed. To generate additional income value addition activity at farm level is a must, especially when price of fresh ginger is too volatile and low.